A model for droplet heating and its implementation into ANSYS Fluent. (August 2016) - Rybdylova, O.; Qubeissi, M. Al; Braun, M.; Crua, C.; Manin, J.; Pickett, L.M.; Sercey, G. de; Sazhina, E.M.; Sazhin, S.S.; Heikal, M.
Abstract: The main ideas of the model for droplet heating and evaporation, based on the analytical solution to the heat conduction equation inside the droplet, and its implementation into ANSYS Fluent are described. The model is implemented into ANSYS Fluent using User-Defined Functions (UDF). The predictions of ANSYS Fluent with the new model are verified against the results predicted by in-house research code for an n -dodecane droplet heated and evaporated in hot air. Also, the predictions of this version of ANSYS Fluent are compared with in-house experimental data.